Thioredoxin-interacting protein (TXNIP) inhibition promotes retinal ganglion cell survival and facilitates M1-like microglial transformation via the PI3K/Akt pathway in glaucoma - Junjue Chen; Huimin Zhong; Bingqiao Shen; Huan Yu; Yang Zhang; Ruiqi Han; Ping Huang; Shouyue Huang; Yisheng Zhong (Molecular Medicine)
Abstract Background Glaucoma is a group of heterogeneous neurodegenerative diseases with abnormal energy metabolism and imbalanced neuroinflammation in the retina. Thioredoxin-interacting protein (TXNIP) is involved in glucose and lipid metabolism, and associated with oxidative stress and inflammation, however, not known whether to be involved in glaucoma neuropathy and its underlying mechanisms. Methods To establish the chronic ocular hypertension (COH) mice model. Western blot, RT-PCR, immunofluorescence and F-VEP were used to detect neuroinflammation level, glial activation and RGCs survival in retina of wild type, TXNIP knockout and MCC950 treatment COH mice. Microglia high-pressure cultured model was constructed. Western blot, RT-PCR and immunofluorescence were used to investigate the proinflammatory cytokines secretion, glucose uptake and phenotype transformation in wild type, TXNIP knockout and overexpressed microglia combined with IL-17A treatment. Finally, we explored the possible underlying mechanisms using relevant pathway inhibitor interventions. Results In this study, for the first time we reported that TXNIP expression was remarkably increased in experimental glaucomatous retina of chronic ocular hypertension (COH) mice, and it was mainly expressed in the ganglion cells layer (GCL). In addition, we found that ablation of TXNIP promoted retinal ganglion cells (RGCs) survival and alleviated visual function impairment in experimental glaucoma. Then, we explored the spatiotemporal consistency between glial activation and retinal inflammation levels in COH mice respectively with TXNIP-deficiency and under treatment of a thermo-containing protein domain 3 (NLRP3) inhibitor MCC950, and the results indicated that TXNIP probably mediated neuroinflammation in glaucomatous retina by activating microglia. Furthermore, upregulation of TXNIP was found in pressure-stimulated microglia, whereas silencing TXNIP facilitated microglial polarization trending towards M1 type and reduced glucose transporter-1 (Glut-1) expression on microglia under high pressure in vitro. Moreover, IL-17A was found to play a role in acting synergistically with TXNIP upon the regulation of microglia polarity transformation. Finally, knockout of TXNIP was revealed to promote PI3K phosphorylation, whereas inhibition of PI3K by LY294002 effectively suppressed Glut-1 expression, glucose uptake, and M1-like transformation tendency in microglia obtained from TXNIP-deficiency mice under high pressure stimulation. Conclusions TXNIP is significantly involved in the inflammation-related neuropathy of experimental glaucoma and probably facilitates M1-like microglial transformation via PI3K/Akt pathway.